Cell death due to chilling injury of mango cultivars ‘Nam Dok Mai No.4’, ‘Nam Dok Mai Si Thong’ and ‘Mahachanok’ during low temperature storage - U. Chanasut (2018)
© 2018 International Society for Horticultural Science. All rights reserved. ‘Nam Dok Mai no. 4’ (NM4), ‘Nam Dok Mai Si Thong’ (NMS) and ‘Mahachanok’ (MCN) are popular cultivars among the exported mangoes from Thailand. These cultivars are usually susceptible to chilling injury (CI) if the storage temperature is lower than 13°C. Several factors such as cultivar or storage temperature had effects on the CI symptoms. This study investigated and compared the CI occurring at the cellular level of three cultivars when stored at either 5 or 8°C. Mango fruits of three cultivars were sampled every week and their physical, anatomical changes of peel and flesh were determined. Results showed that NM4, MCN and NMS were susceptible to CI at 5°C. The symptoms such as surface pitting, peel browning, abnormal ripening and disease incidents occurred after storage at 5°C for 3, 3 and 2 weeks, respectively. Similar symptoms occurred on MCN kept at 8°C for 3 weeks, but did not occur on NMS and NM4. Cell viability tests using Evans blue solution indicated that dead cells which had intact membrane were found in the flesh on the seed side prior to the flesh on the peel side. It occurred in the flesh of NMS and MCN stored at 5°C and in the MCN flesh after storage at 8°C for 2 weeks. Furthermore, the cell death occurred prior to the onset of CI symptoms, with electrolyte leakage and malondialdehyde content increasing. It is possible to conclude that these mango cultivars did not affect the development of CI symptoms, but they may affect CI sensitivity which takes place at the cellular level.